Red Blood Cell Membrane Processing for Biomedical Applications - Rossi, Luigia; Fraternale, Alessandra; Bianchi, Marzia; Magnani, Mauro (Frontiers in Physiology, 2019)
Red blood cells (RBC) are actually exploited as innovative drug delivery systems with unconventional and convenient properties. Because of a long in vivo survival and a non-random removal from circulation, RBC can be loaded with drugs and/or contrasting agents without affecting these properties and maintaining the original immune competence. However, native or drug-loaded RBC, can be modified decorating the membrane with peptides, antibodies or small chemical entities so favoring the targeting of the processed RBC to specific cells or organs. Convenient modifications have been exploited to induce immune tolerance or immunogenicity, to deliver antibodies capable of targeting other cells, and to deliver a number of constructs that can recognize circulating pathogens or toxins. The methods used to induce membrane processing useful for biomedical applications include the use of crosslinking agents and bifunctional antibodies, biotinylation and membrane insertion. Another approach includes the expression of engineered membrane proteins upon ex vivo transfection of immature erythroid precursors with lentiviral vectors, followed by in vitro expansion and differentiation into mature erythrocytes before administration to a patient in need. Several applications have now reached the clinic and a couple of companies that take advantage from these properties of RBC are already in Phase 3 with selected applications. The peculiar properties of the RBC and the active research in this field by a number of qualified investigators, have opened new exciting perspectives on the use of RBC as carriers of drugs or as cellular therapeutics.